Supporting frontline workers in the biodiversity crisis by empowering and enabling practitioners to embrace conservation evidence - Steven J. Cooke; Kevin A. Adeli; Trina Rytwinski; Andrew N. Kadykalo; Jennifer F. Provencher; Vivian M. Nguyen; Joseph R. Bennett; Christina M. Davy; Rachel T. Buxton; Dalal E. L. Hanna; Nathan Young; Jesse C. Vermaire; et al. (Socio-Ecological Practice Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Integration of Indigenous practices into fisheries legislation: Obstacles and opportunities for the maramataka (Māori lunar calendar) - Louise Bennett-Jones; Christopher D. Hepburn; Brendan Flack; Nigel J. Scott; Gaya Gnanalingam (Marine Policy, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Acute Toxicity of 6PPDQ, 6PPD, and Other Transformation Products to a Freshwater Mussel (Lampsilis siliquoidea, Barnes 1823) - David J. Soucek; Rebecca A. Dorman; Jeffery A. Steevens; Viviane Yargeau; Marco Pineda; Christopher D. Metcalfe; Erin R. Bennett (Bulletin of Environmental Contamination and Toxicology, 2026)

BMP9 knockout impairs pulmonary vessel muscularisation and confers aberrant tamoxifen sensitivity - Benjamin J. Dunmore; Stephen Moore; Rowena J. Jones; Joshua Hodgson; Kathryn Auckland; Mark Southwood; Nichola Figg; Nobuhiro Kikuchi; Martin Bennett; Allan Lawrie; Christopher J. Rhodes; Mark R. Toshner; et al. (Angiogenesis, 2025)
Deleterious mutations in the GDF2 gene, encoding BMP9, are causative of pulmonary arterial hypertension and hereditary haemorrhagic telangiectasia. Paradoxically, BMP9 germ-line knockout ( Gdf2 −/− ; Bmp9 KO) and double Bmp9 KO / conditional Bmp10 cKO (dKO) mice exhibit an attenuated response to PAH-inducing stimuli. We asked whether this contradiction is due to the pathological, physiological, or genetic consequences of BMP9 knockout. In Bmp9 KO mice we observed reduced pulmonary vascular smooth muscle cell (SMC) coverage and using RNA-seq analysis of Bmp9 KO mouse lungs identified two novel genes, COLQ and ITGA6 , which were differentially regulated in a human PAH RNA-seq dataset. In order to study BMP10 loss, postnatal tamoxifen treatment was required to induce Bmp10 cKO. As previously reported, in dKO mice we observed cardiomegaly and splenomegaly, as well as hyperplasia and hemosiderosis in the pulmonary vasculature. Surprisingly, tamoxifen treated Bmp9 KO control mice phenocopied these pathological changes in dKO mice and downregulated SMC marker gene transcription. Loss of BMP10 is not critical for severe tissue remodelling in the lung, heart, and spleen, rather Bmp9 KO mice appear sensitive to tamoxifen and BMP9 loss is the primary cause of mild vessel remodelling due to a basal reduction of smooth muscle cell coverage. This study suggests that interaction of the BMP pathway with tamoxifen needs to be carefully considered when studying Bmp9 KO mice and urges caution in the context of tamoxifen use when studying cardiovascular and pulmonary disease models.

Flow structure and mixing near a small river plume front: Winyah Bay, SC, USA - Christopher Papageorgiou; George Voulgaris; Alexander E. Yankovsky; Diane Bennett Fribance (Ocean Science, 2025)
This study presents Eulerian data from Winyah Bay, SC, USA collected during the passage of a tidal plume. The data captured the evolution and structure of the plume and include high-resolution velocity and temperature time series, supplemented by temperature – salinity profiles from a MicroCTD profiler. The observations identified a pre-existing plume extending to 4 m, with a water density of 1023.6 kg m−3, laying above denser ambient waters. Upon arrival, the newly discharged tidal plume introduced a fresher layer (1020.7 kg m−3) extending to 2.6 m, gradually thinning due to radial spreading. The plume's frontal propagation measured at 0.36 m s−1 with a calculated Froude number of 1.32, indicating gravity current dynamics. In the across-front direction a return flow developed under the plume that extended throughout the water column, resembling an estuarine-like circulation pattern. Mixing processes were examined using the available overturn potential energy (AOPE) in the water column as described in Smith (2020). The analysis showed that near the bed, bottom boundary layer turbulence is the main mixing mechanism both before and after the passage of the front. In the surface layer, before the arrival of the front, mixing is driven by wind-induced shear and overturning. Within the gravity current, despite the high turbulent kinetic energy dissipation rates in certain regions, shear-induced mixing was minimal. These findings were reflected in the density diffusivity estimates near the surface that varied from 10−6 m2 s−1 prior to the arrival of the front, increasing to 10−5 m2 s−1 very near the front and diminishing to 10−10 m2 s−1 within the plume despite the high velocity shear observed there. The limited mixing within the plume despite the high shear observed can be explained using the concept of a layer-interface structure, where layers of high turbulence and low stratification alternate with regions of low turbulence and higher stratification. Although not resolved by these observations, this structure has been observed in numerical simulations of mixing. The development of the counter-flow under the plume suggests that tide and/or wind induced straining may play an important role in enhancing stratification in plumes like the one studied here.

Calibration of the FullCAM model for Australian native vegetation - David I. Forrester; Jacqueline R. England; Chiara Pasut; Keryn I. Paul; Lauren T. Bennett; Chris Eastaugh; Thomas Fairman; Melissa Fedrigo; Carl R. Gosper; Sabine Kasel; Tom Lewis; Crispen Marunda; et al. (Ecological Modelling, 2025)

Genome-wide associations within diverse wild apple germplasm for postharvest blue mold resistance to Penicillium expansum - Lauren Whitt; John S. Bennett; Tamara D. Collum; Breyn Evans; Doug Raines; Ben Gutierrez; Wojciech J. Janisiewicz; Wayne M. Jurick; Christopher Gottschalk (Postharvest Biology and Technology, 2025)

Photothermal spectroscopy for planetary sciences: Mid-IR absorption made easy - Christopher Cox; Jakob Haynes; Christopher Duffey; Christopher Bennett; Julie Brisset (Planetary and Space Science, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Centering community values in marine planning - Fiona Beaty; Bridget John; Myia Antone; Jonathan Williams; Nathan Bennett; Nikita Wallia; Christopher Harley (Marine Policy, 2024)

Analysis of the Atomistic MD Simulations of CI+CIII2 Interactions and Associated Lipid Binding - Amina Djurabekova; Young-Cheul Shin; Pedro Latorre-Muro; Oleksii Zdorevskyi; Christopher F. Bennett; Nils Burger; Kangkang Song; Chen Xu; Maofu Liao; Pere Puigserver; Vivek Sharma (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Consumer purchase response to e-bike incentives: Results from a nationwide stated preference study - Luke R. Jones; Cameron Bennett; John H. MacArthur; Christopher R. Cherry (Transportation Research Part D: Transport and Environment, 2024)

Correction to: The Kelp Forest Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh‑Dalmau; Nina Larissa Arroyo; Anne M. Bauer‑Civiello; Rodrigo Beas‑Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)

The Kelp Forest ﻿Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh-Dalmau; Nina Larissa Arroyo; Anne M. Bauer-Civiello; Rodrigo Beas-Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)
Marine kelp forests cover 1/3 of our world's coastlines, are heralded as a nature-based solution to address socio-environmental issues, connect hundreds of millions of people with the ocean, and support a rich web of biodiversity throughout our oceans. But they are increasingly threatened with some areas reporting over 90% declines in kelp forest cover in living memory. Despite their importance and the threats they face, kelp forests are entirely absent from the international conservation dialogue. No international laws, policies, or targets focus on kelp forests and very few countries consider them in their national policy. The Kelp Forest Challenge addresses that gap. Together with 252 kelp experts, professionals, and citizens from 25 countries, the Kelp Forest Challenge was developed as a grassroots vision of what the world can achieve for kelp forest conservation. It is a global call to restore 1 million and protect 3 million hectares of kelp forests by 2040. This is a monumental challenge, that will require coordination across multiple levels of society and the mobilization of immense resources. Pledges may therefore include area for protection or restoration, enabling pledges which assist in conservation (funding, equipment, professional expertise, capacity building), or awareness-based pledges which increase awareness or education about kelp forests. Correspondingly, participants may be from government, scientific institutions, private sector, NGOs, community groups, or individuals. This challenge is the beginning of a 17-year mission to save our kelp forests and anyone and any organisation is invited to participate.

Elevated pro-inflammatory cytokines and chemokines in saliva of cats with feline odontoclastic resorptive lesion - Sheeba Thomas; David Francis Lappin; David Bennett; Christopher Nile; Marcello Pasquale Riggio (Research in Veterinary Science, 2024)

Data-driven method for electric vehicle charging demand analysis: Case study in Virginia - Zhaocai Liu; Brennan Borlaug; Andrew Meintz; Christopher Neuman; Eric Wood; Jesse Bennett (Transportation Research Part D: Transport and Environment, 2023)

Method of test for CO2-based demand control ventilation systems: Benchmarking the state-of-the-art and the undervalued potential of proportional-integral control - Theresa Pistochini; Matthew Ellis; Fredrick Meyers; Antonea Frasier; Christopher Cappa; Deborah Bennett (Energy and Buildings, 2023)

Chow diet in mouse aging studies: nothing regular about it - Jennifer Lee; Chloe Purello; Sarah L. Booth; Brian Bennett; Christopher D. Wiley; Ron Korstanje (GeroScience, 2023)
Chow diet is used in the majority of rodent studies and, although assumed to be standardized for dietary source and nutritional contents, it varies widely across commercial formulations. Similarly, current approaches to study aging in rodents involve a single-diet formulation across the lifespan and overlook age-specific nutritional requirements, which may have long-term effects on aging processes. Together, these nutrition-based disparities represent major gaps in geroscience research, affecting the interpretation and reproducibility of the studies. This perspective aims to raise awareness on the importance of rodent diet formulation and proposes that geroscientists include detailed descriptions of all experimental diets and feeding protocols. Detailed reporting of diets will enhance rigor and reproducibility of aging rodent studies and lead to more translational outcomes in geroscience research.

Infection‐competent monkeypox virus contamination identified in domestic settings following an imported case of monkeypox into the UK - Barry Atkinson; Christopher Burton; Thomas Pottage; Katy‐Anne Thompson; Didier Ngabo; Ant Crook; James Pitman; Sian Summers; Kuiama Lewandowski; Jenna Furneaux; Katherine Davies; Timothy Brooks; et al. (Environmental Microbiology, 2022)
An imported case of monkeypox was diagnosed in December 2019 in a traveller returning from Nigeria to the UK. Subsequently, environmental sampling was performed at two adjoining single‐room residences occupied by the patient and their sibling. Monkeypox virus DNA was identified in multiple locations throughout both properties, and monkeypox virus was isolated from several samples 3 days after the patient was last in these locations. Positive samples were identified following the use of both vacuum and surface sampling techniques; these methodologies allowed for environmental analysis of potentially contaminated porous and non‐porous surfaces via real‐time quantitative reverse transcriptase PCR analysis in addition to viral isolation to confirm the presence of infection‐competent virus. This report confirms the potential for infection‐competent monkeypox virus to be recovered in environmental settings associated with known positive cases and the necessity for rapid environmental assessment to reduce potential exposure to close contacts and the general public. The methods adopted in this investigation may be used for future confirmed cases of monkeypox in order to establish levels of contamination, confirm the presence of infection‐competent material and to identify locations requiring additional cleaning.

Nitrogen and Sulfur Deposition Reductions Projected to Partially Restore Forest Soil Conditions in the US Northeast, While Understory Composition Continues to Shift with Future Climate Change - Stephen D. LeDuc; Christopher M. Clark; Jennifer Phelan; Salim Belyazid; Micah G. Bennett; Katie Boaggio; John Buckley; Jamie Cajka; Phillip Jones (Water, Air, & Soil Pollution, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Flexibility for fuelling reproduction in a pelagic ray ( Mobula eregoodoo ) suggested by bioenergetic modelling - Christopher L Lawson; Christine L Dudgeon; Anthony J Richardson; Matt K Broadhurst; Michael B Bennett (Journal of Fish Biology, 2022)
This study investigated the measurements of energy density and bioenergetic modelling for a pelagic ray, Mobula eregoodoo , to estimate its relative allocation to various bodily processes and especially reproduction. The data revealed M. eregoodoo uses up to 21.0% and 2.5% of its annual energy budget on growth and reproduction, respectively. During pregnancy, females depleted energy reserves in the liver, which, along with their biennial reproductive cycle, aligns with general theory that ectotherms are capital breeders and thus build energy reserves before reproduction. Nonetheless, the reduction in energy reserves did not account for all reproductive costs, and therefore, gravid females supplement reproductive costs through energy derived from the diet, according to an income‐breeding strategy. These characteristics imply that M. eregoodoo exhibits some flexibility in fuelling reproduction depending on energy availability throughout the reproductive cycle, which may be prevalent in other elasmobranchs. The data represent the first estimates of both the metabolic costs of gestation in elasmobranchs and the relative cost of reproduction in rays. Energy costs and plasticity associated with highly variable reproductive strategies in elasmobranchs may influence long‐term population viability under a rapidly changing environment.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Recognize fish as food in policy discourse and development funding - Abigail Bennett; Xavier Basurto; John Virdin; Xinyan Lin; Samantha J. Betances; Martin D. Smith; Edward H. Allison; Barbara A. Best; Kelly D. Brownell; Lisa M. Campbell; Christopher D. Golden; Elizabeth Havice; et al. (Ambio, 2021)
The international development community is off-track from meeting targets for alleviating global malnutrition. Meanwhile, there is growing consensus across scientific disciplines that fish plays a crucial role in food and nutrition security. However, this ‘fish as food’ perspective has yet to translate into policy and development funding priorities. We argue that the traditional framing of fish as a natural resource emphasizes economic development and biodiversity conservation objectives, whereas situating fish within a food systems perspective can lead to innovative policies and investments that promote nutrition-sensitive and socially equitable capture fisheries and aquaculture. This paper highlights four pillars of research needs and policy directions toward this end. Ultimately, recognizing and working to enhance the role of fish in alleviating hunger and malnutrition can provide an additional long-term development incentive, beyond revenue generation and biodiversity conservation, for governments, international development organizations, and society more broadly to invest in the sustainability of capture fisheries and aquaculture.

Coral loss alters guarding and farming behavior of a Caribbean damselfish - Valentina Di Santo; Lois A. O’Boyle; Ryan K. Saylor; Theresa F. Dabruzzi; Marthe A. Covell; Katrina Kaack; Rachel Scharer; Katherine Seger; Nicholas Favazza; Christopher M. Pomory; Wayne A. Bennett (Marine Biology, 2020)
Coral loss is a major element of global ecological change in the oceans that may shape the behavior of keystone species such as habitat-attached animals. Farming damselfishes cultivate and aggressively protect algal garden within their territory, thereby shaping local fish assemblages and macro-algae diversity. Following the widespread loss of live branching coral throughout Florida and the Caribbean Sea, dusky damselfish ( Stegastes adustus ) have modified their territorial behavior. We compared antagonistic behavior, and size and algal species composition of territories of dusky damselfish on dead branching coral rubble and live boulder coral in the Dry Tortugas National Park, USA. Even though similar numbers of “intruders” entered each habitat type, dusky damselfish on rubble territories chased out significantly more fishes, had larger territories and more species of algae were present in their gardens. This study shows that dusky damselfish successfully occupy living and dead coral areas; however, there are potential trade-offs between defending a larger territory and cultivating fewer algal species.

Patient- and area-level predictors of prostate cancer among South Carolina veterans: a spatial analysis - Peter Georgantopoulos; Jan M. Eberth; Bo Cai; Christopher Emrich; Gowtham Rao; Charles L. Bennett; Kathlyn S. Haddock; James R. Hébert (Cancer Causes & Control, 2020)

The provision and utility of earth science to decision-makers: synthesis and key findings - Mark C. Quigley; Luke G. Bennetts; Patricia Durance; Petra M. Kuhnert; Mark D. Lindsay; Keith G. Pembleton; Melanie E. Roberts; Christopher J. White (Environment Systems and Decisions, 2019)

The provision and utility of science and uncertainty to decision-makers: earth science case studies - Mark C. Quigley; Luke G. Bennetts; Patricia Durance; Petra M. Kuhnert; Mark D. Lindsay; Keith G. Pembleton; Melanie E. Roberts; Christopher J. White (Environment Systems and Decisions, 2019)

Voluntary Restoration: Mitigation's Silent Partner in the Quest to Reverse Coastal Wetland Loss in the USA - Rachel K. Gittman; Christopher J. Baillie; Katie K. Arkema; Richard O. Bennett; Jeff Benoit; Seth Blitch; Julien Brun; Anthony Chatwin; Allison Colden; Alyssa Dausman; Bryan DeAngelis; Nathaniel Herold; et al. (Frontiers in Marine Science, 2019)

Sex Differences in Gene and Protein Expression After Intracerebral Hemorrhage in Mice - Yongqiu Xie; Yi-Ju Li; Beilei Lei; Dawn Kernagis; Wen-Wei Liu; Ellen R. Bennett; Talagnair Venkatraman; Christopher D. Lascola; Daniel T. Laskowitz; David S. Warner; Michael L. James (Translational Stroke Research, 2019)

Rare loss of function variants in candidate genes and risk of colorectal cancer - Elisabeth A. Rosenthal; Brian H. Shirts; Laura M. Amendola; Martha Horike-Pyne; Peggy D. Robertson; Fuki M. Hisama; Robin L. Bennett; Michael O. Dorschner; Deborah A. Nickerson; Ian B. Stanaway; Rami Nassir; Kathy T. Vickers; et al. (Human Genetics, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Equity trade‐offs in conservation decision making - Elizabeth A. Law; Nathan J. Bennett; Christopher D. Ives; Rachel Friedman; Katrina J. Davis; Carla Archibald; Kerrie A. Wilson (Conservation Biology, 2018)
Conservation decisions increasingly involve multiple environmental and social objectives, which result in complex decision contexts with high potential for trade‐offs. Improving social equity is one such objective that is often considered an enabler of successful outcomes and a virtuous ideal in itself. Despite its idealized importance in conservation policy, social equity is often highly simplified or ill‐defined and is applied uncritically. What constitutes equitable outcomes and processes is highly normative and subject to ethical deliberation. Different ethical frameworks may lead to different conceptions of equity through alternative perspectives of what is good or right. This can lead to different and potentially conflicting equity objectives in practice. We promote a more transparent, nuanced, and pluralistic conceptualization of equity in conservation decision making that particularly recognizes where multidimensional equity objectives may conflict. To help identify and mitigate ethical conflicts and avoid cases of good intentions producing bad outcomes, we encourage a more analytical incorporation of equity into conservation decision making particularly during mechanistic integration of equity objectives. We recommend that in conservation planning motivations and objectives for equity be made explicit within the problem context, methods used to incorporate equity objectives be applied with respect to stated objectives, and, should objectives dictate, evaluation of equity outcomes and adaptation of strategies be employed during policy implementation.

Mechanical perturbations can elicit triggered reactions in the absence of a startle response - Christopher J. Forgaard; Ian M. Franks; Kimberly Bennett; Dana Maslovat; Romeo Chua (Experimental Brain Research, 2018)

Site Selection: a Case Study in the Identification of Optimal Cysteine Engineered Antibody Drug Conjugates - L. Nathan Tumey; Fengping Li; Brian Rago; Xiaogang Han; Frank Loganzo; Sylvia Musto; Edmund I. Graziani; Sujiet Puthenveetil; Jeffrey Casavant; Kimberly Marquette; Tracey Clark; Jack Bikker; et al. (The AAPS Journal, 2017)

Signal-to-noise ratio improvement of swept-tone-generated transient otoacoustic emissions - Christopher L. Bennett; Todor Mihajloski; Özcan Özdamar (Medical & Biological Engineering & Computing, 2017)

The effect of age and microstructural white matter integrity on lap time variation and fast-paced walking speed - Qu Tian; Luigi Ferrucci; Susan M. Resnick; Eleanor M. Simonsick; Michelle D. Shardell; Bennett A. Landman; Vijay K. Venkatraman; Christopher E. Gonzalez; Stephanie A. Studenski (Brain Imaging and Behavior, 2016)

Cognitive activity, cognitive function, and brain diffusion characteristics in old age - Konstantinos Arfanakis; Robert S. Wilson; Christopher M. Barth; Ana W. Capuano; Anil Vasireddi; Shengwei Zhang; Debra A. Fleischman; David A. Bennett (Brain Imaging and Behavior, 2016)

The potential for indirect effects between co‐flowering plants via shared pollinators depends on resource abundance, accessibility and relatedness - Luísa Gigante Carvalheiro; Jacobus Christiaan Biesmeijer; Gita Benadi; Jochen Fründ; Martina Stang; Ignasi Bartomeus; Christopher N. Kaiser‐Bunbury; Mathilde Baude; Sofia I. F. Gomes; Vincent Merckx; Katherine C. R. Baldock; Andrew T. D. Bennett; et al. (Ecology Letters, 2014)
Co‐flowering plant species commonly share flower visitors, and thus have the potential to influence each other's pollination. In this study we analysed 750 quantitative plant–pollinator networks from 28 studies representing diverse biomes worldwide. We show that the potential for one plant species to influence another indirectly via shared pollinators was greater for plants whose resources were more abundant (higher floral unit number and nectar sugar content) and more accessible. The potential indirect influence was also stronger between phylogenetically closer plant species and was independent of plant geographic origin (native vs. non‐native). The positive effect of nectar sugar content and phylogenetic proximity was much more accentuated for bees than for other groups. Consequently, the impact of these factors depends on the pollination mode of plants, e.g. bee or fly pollinated. Our findings may help predict which plant species have the greatest importance in the functioning of plant–pollination networks.

Small Molecule Specific Run Acceptance, Specific Assay Operation, and Chromatographic Run Quality Assessment: Recommendation for Best Practices and Harmonization from the Global Bioanalysis Consortium Harmonization Teams - Eric J. Woolf; Stuart McDougall; Douglas M. Fast; Maristela Andraus; Matthew Barfield; Michael Blackburn; Ben Gordon; David Hoffman; Noriko Inoue; Gabriel Marcelin-Jimenez; Amy Flynn; Richard LeLacheur; et al. (The AAPS Journal, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Performance of an empirical bias‐correction of a high‐resolution climate dataset - James C. Bennett; Michael R. Grose; Stuart P. Corney; Christopher J. White; Gregory K. Holz; Jack J. Katzfey; David A. Post; Nathaniel L. Bindoff (International Journal of Climatology, 2014)
We describe the method and performance of a bias‐correction applied to high‐resolution (˜10 km) simulations from a stretched‐grid Regional Climate Model ( RCM ) over Tasmania, Australia. The bias‐correction is a quantile mapping of empirical cumulative frequency distributions. Corrections are applied at a daily time step to five variables: rainfall, potential evaporation (PE), solar radiation, maximum temperature and minimum temperature. Corrections are calculated independently for each season. We show that quantile mapping of empirical distributions can be highly effective in correcting biases in RCM outputs. Cross‐validation shows biases are effectively reduced across the range of cumulative frequency distributions, with few exceptions. The bias‐correction is not as effective at correcting biases for values at or near zero (e.g. in rainfall simulations), although even here the bias‐correction improves biases evident in the uncorrected simulations. In addition, the bias‐correction improves frequency characteristics of variables such as the number of rain days. We use a detrending technique to apply the bias‐correction to 140‐year time series of RCM variables. We show that the bias‐correction effectively preserves long‐term changes (e.g. to the mean and variance) to variables projected by the uncorrected RCM simulations. Correlations between key variables are also largely preserved, thus the bias‐corrected outputs reflect the dynamics of the underlying RCM . However, the bias‐corrected simulations still exhibit some of the deficiencies of the RCM simulations, e.g. the tendency to underestimate the magnitude and duration of large, multi‐day rain events, and the tendency to underestimate the duration of dry spells. The bias‐corrected simulations for six downscaled GCMs for the A2 and B1 emissions scenarios are available to researchers from http://www.tpac.org.au .

New information on body size and cranial display structures of Pterodactylus antiquus, with a revision of the genus - S. Christopher Bennett (PalZ, 2013)

A regional response in mean westerly circulation and rainfall to projected climate warming over Tasmania, Australia - Michael R. Grose; Stuart P. Corney; Jack J. Katzfey; James C. Bennett; Gregory K. Holz; Christopher J. White; Nathaniel L. Bindoff (Climate Dynamics, 2013)

Perception of 3-D location based on vision, touch, and extended touch - Nicholas A. Giudice; Roberta L. Klatzky; Christopher R. Bennett; Jack M. Loomis (Experimental Brain Research, 2013)

TOMM40 in Cerebral Amyloid Angiopathy Related Intracerebral Hemorrhage: Comparative Genetic Analysis with Alzheimer’s Disease - Valerie Valant; Brendan T. Keenan; Christopher D. Anderson; Joshua M. Shulman; William J. Devan; Alison M. Ayres; Kristin Schwab; Joshua N. Goldstein; Anand Viswanathan; Steven M. Greenberg; David A. Bennett; Philip L. De Jager; et al. (Translational Stroke Research, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

The metal ion requirements of Arabidopsis thaliana Glx2-2 for catalytic activity - Pattraranee Limphong; Ross M. McKinney; Nicole E. Adams; Christopher A. Makaroff; Brian Bennett; Michael W. Crowder (JBIC Journal of Biological Inorganic Chemistry, 2010)

Angular momentum synergies during walking - Thomas Robert; Bradford C. Bennett; Shawn D. Russell; Christopher A. Zirker; Mark F. Abel (Experimental Brain Research, 2009)

A second specimen of the pterosaurAnurognathus ammoni - S. Christopher Bennett (PalZ, 2007)

Colony structure and parentage in wild colonies of co‐operatively breeding Damaraland mole‐rats suggest incest avoidance alone may not maintain reproductive skew - TAMSIN M. BURLAND; NIGEL C. BENNETT; JENNIFER U. M. JARVIS; CHRISTOPHER G. FAULKES (Molecular Ecology, 2004)
Colonies of co‐operatively breeding African mole‐rats have traditionally been thought to be composed of a single breeding female, one or two breeding males, and their offspring. In the naked mole‐rat ( Heterocephalus glaber ), the occurrence of facultative inbreeding means incest avoidance cannot prevent reproduction in subordinate group members, and physiological suppression of reproductive function by the breeding female occurs in both sexes. In contrast, previous studies of captive colonies of the Damaraland mole‐rat ( Cryptomys damarensis ) suggest that breeding within a colony is restricted to a single breeding pair, simply because all other colony members are highly related (first‐ or second‐order relatives) and this species is an obligate outbreeder. Using microsatellite markers, we investigated parentage and colony composition in 18 wild Damaraland mole‐rat colonies to determine whether inbreeding avoidance alone can explain the high levels of reproductive skew in this species. Multiple and unidentified paternity was widespread within colonies and immigrants of both sexes were regularly identified. Unrelated, opposite‐sex nonbreeders were found coexisting in two colonies. These results suggest that, in the wild, conditions exist where nonreproductive females can come into contact with unrelated males, even when they do not disperse from their natal colony. Inbreeding avoidance alone is therefore insufficient to maintain the high levels of reproductive skew identified in this species suggesting that the breeding female somehow suppresses the reproductive function in nonbreeding females.

New crested specimens of the Late Cretaceous pterosaurNyctosaurus - S. Christopher Bennett (PalZ, 2003)

A novel locus for Meckel-Gruber syndrome, MKS3 , maps to chromosome 8q24 - Neil Morgan; Paul Gissen; Saghira Sharif; Laura Baumber; Joan Sutherland; Deirdre Kelly; Kingi Aminu; Christopher Bennett; Geoffrey Woods; Robert Mueller; Richard Trembath; Eamonn Maher; et al. (Human Genetics, 2002)

Land-Use Dynamics in a Southern Illinois (USA) Watershed - CHRISTOPHER LANT; TIMOTHY LOFTUS; STEVEN KRAFT; DAVID BENNETT (Environmental Management, 2001)

Non-erythroid form of acute intermittent porphyria caused by promoter and frameshift mutations distant from the coding sequence of exon 1 of the HMBS gene - Sharon D. Whatley; Andrew G. Roberts; David H. Llewellyn; Christopher P. Bennett; Christine Garrett; George H. Elder (Human Genetics, 2000)

Perceptions of Species Abundance, Distribution, and Diversity: Lessons from Four Decades of Sampling on a Government-Managed Reserve - J. Whitfield Gibbons; Vincent J. Burke; Jeffrey E. Lovich; Raymond D. Semlitsch; Tracey D. Tuberville; J. Russell Bodie; Judith L. Greene; Peter H. Niewiarowski; Howard H. Whiteman; David E. Scott; Joseph H. K. Pechmann; Christopher R. Harrison; et al. (Environmental Management, 1997)